PECULIARITIES OF ACCUMULATION OF POLLUTANTS IN PLANTS OF ROADSIDE STRIPS OF CHERNIVTSI REGION - KOVBINKA, Halyna (My University, 2023)
The vegetation cover of road geosystems in Chernivtsi oblast was formed under the influence of natural and anthropogenic factors. The location of the region's territory in three physical and geographical areas indicates the diversity of natural vegetation along the roads that cross the region.
Keywords: : landscape, geochemical zoning, settlement landscape, natural landscape.